Factors Associated with Health Seeking Behavior among Women of Reproductive Age in Slum Areas of Pokhara Metropolitan - Rakshita Lamichhane; Bimala Bhatta; Namuna Sharma (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Women’s health seeking behavior can be determined through various factors such as socio-demographic, economic, health condition etc. The objective of this study is to assess the factors associated with health seeking behavior among women of reproductive age in slum areas of Pokhara Metropolitan. MATERIAL AND METHODS Cross-sectional analytical study design was used to assess the health seeking behavior among 350 reproductive age women population in Pokhara Metropolitan from June to December 2019. Purposive sampling was used to collect the samples. Face to face interview was used as data collection technique and semi structured questionnaires were used as data collection tools. Data were entered in EPI-DATA and analyzed using SPSS as per data analysis plan. RESULTS The mean age of the participant was 31 years and majority of the participants belonged to age group 25-35. Majority of the participant 80.6% were Hindu, 41.1% had basic education, 73.4% were married and 97.1% were living along with their family. No variables were found having association with health seeking behavior. Majority 57% women who were ill for >30 days sought for their health care. More than half of the women i.e. 54% preferred nearby medicals/clinics as their treatment place. CONCLUSION The overall health seeking behavior was good in this study area. Most of the participants had knowledge on visit to health facility when ill. Most of the participants were serious about their health issues.